Efektivitas Konseling Krisis Pendekatan Realita untuk Meningkatkan Penerimaan Diri pada Anak Broken Home - Tohari, Sabit; Aminah, Aminah (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2023)
Adolescents, particularly teenage girls, from families that have undergone divorce, tend to exhibit emotional vulnerability when faced with adverse situations. For instance, parental divorce can lead to changes in a teenage girl's attitudes, thoughts, and behaviors. This study seeks to determine whether crisis counseling, employing a reality-based approach, can enhance self-acceptance in children from divorced households. The research methodology employed is a quantitative quasi-experimental design, specifically a one-group pre-test and post-test experimental design. The rationale behind choosing this experimental design is to assess the impact of the intervention. Data analysis techniques, specifically the T Test, are utilized to evaluate the effectiveness of crisis counseling with a reality-based approach in improving self-acceptance among children who have experienced parental divorce. The findings of the study indicate that there is a statistically significant improvement in self-acceptance among children from divorced families who undergo crisis counseling with a reality-based approach. In summary, crisis counseling employing a reality-based approach proves to be a reasonably effective method for enhancing self-acceptance in children from divorced households. Keywords: Reality crisis counesling;Accepting yourself;Broken hoome